Synthesis and characterization of chitosan-saponin nanoparticle for application in plasmid DNA delivery - Bande, Faruku; Arshad, Siti Suri; Mohd Hair Bejo; Kamba, Shafiu Abdullahi; Omar, Abdul Rahman (Hindawi Publishing Corporation, 2015)
Nonviral delivery system receives attention over the last decade. Chitosan (CS) is a cationic polymer whereas saponin (SP) is classified as glycoside. In this study, a spherically-shaped CS-SP nanoparticle was synthesized and characterized. The ability of the nanoparticle to protect DNA from enzymatic degradation, its thermostability and cytotoxicity were evaluated. The particle size was found below 100 nm as determined by Zetasizer, transmission electron microscopy (TEM), and field scanning electron microscopy (FSEM) results. The surface charge ranges from 43.7 mV to 38.5 mV before and after encapsulation with DNA plasmid, respectively. In terms of thermostability, Thermal Gravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC) revealed that CS-SP nanoparticle had a melting temperature of 110°C, with rapid decomposition occurring at 120°C. Encapsulation of DNA with the synthesized nanoparticle was evidenced by changes in the FTIR spectra including characteristic peaks at 3267.39 and 1635.58 cm−1, wavenumbers. Additional peak was also observed at 1169.7 cm−1 following encapsulation. Electrophoretic mobility showed that CS-SP nanoparticle protected plasmid DNA from enzymatic degradation, while cell viability assays confirmed that the synthesized nanoparticle exhibited low cytotoxicity at different concentrations in avian cells. Taken together these, CS-SP nanoparticle showed potentials for applications as a DNA delivery system.